1984
DOI: 10.1017/s0021859600043458
|View full text |Cite
|
Sign up to set email alerts
|

Water use by winter wheat as affected by soil management

Abstract: SummaryIn each of the years from September 1977 to July 1982 winter wheat was grown on one or more of three clay soil sites (clay content 35–55%) in Oxfordshire where the climate is close to the average for the area of England growing winter cereals.The effects on crop water use of different soil management practices, including ploughing, direct drilling and subsoil drainage, are compared. Cultivation treatment had little effect on the maximum depth of water extraction, which on average in these clay soils was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Stubble management had no effect on either evapotranspiration (ET) or WUE of soybean. Goss et al (1984) O'sullivan (1995) observed that in a humid environment on land cropped to spring bjrrley most changes in soil water occurred in the top 0.4 m. The rate of soil drying was greater when the land was plowed prior to seeding than when seeding was by direct drilling; however, the greater water uptake from topsoil by spring barley grown on the plowed treatment, did not increase yields. In a subhumid environment, Maul6 and Chanasyk (1987) (Fig.…”
mentioning
confidence: 99%
“…Stubble management had no effect on either evapotranspiration (ET) or WUE of soybean. Goss et al (1984) O'sullivan (1995) observed that in a humid environment on land cropped to spring bjrrley most changes in soil water occurred in the top 0.4 m. The rate of soil drying was greater when the land was plowed prior to seeding than when seeding was by direct drilling; however, the greater water uptake from topsoil by spring barley grown on the plowed treatment, did not increase yields. In a subhumid environment, Maul6 and Chanasyk (1987) (Fig.…”
mentioning
confidence: 99%
“…Some 66% of the precipitation was intercepted by the mole and pipe‐drain system in the same period (Table 1). In the spring and summer, a greater volume of water was extracted by wheat crops from lysimeters where the mole drains removed water from the top 0.5 m during the autumn and winter months (Goss et al. , 1984).…”
Section: Hydrologic Studiesmentioning
confidence: 99%
“…The reciprocal of this relationship is the transpiration ratio, and for this forage corn crop it is 112 L H 2 O/kg dry matter. On the field scale lysimeters of Letcombe Laboratory, Goss et al. (1984) reported water use efficiencies for winter wheat of 0.0052 kg/L H 2 O.…”
Section: Evaporation and Transpirationmentioning
confidence: 99%
“…The importance of drought in limiting the yield of winter wheat in the UK was actively debated in the late 1970s when the Agricultural Research Council started the 4-Institute Yield Variation Programme. This led to a review of the results of earlier irrigation experiments by Gales (1 983), new measurements of water use by irrigated (Prew et af., 1983(Prew et af., , 1985 and unirrigated crops (Goss et al, 1984) and the testing of drought-resistant varieties (Innes 8i Blackwell, 1983). Other activities included the measurement of the growth of *Rothamsted Experimental Station, Harpenden, Hem, AL5 2JQ.…”
mentioning
confidence: 99%